2019
DOI: 10.1186/s12889-019-6877-z
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of adherence to physical activity interventions among three chronic conditions: cancer, cardiovascular disease, and diabetes

Abstract: Background Physical activity is effective for the prevention and treatment of chronic disease, yet insufficient evidence is available to make comparisons regarding adherence to aerobic physical activity interventions among chronic disease populations, or across different settings. The purpose of this review is to investigate and provide a quantitative summary of adherence rates to the aerobic physical activity guidelines among people with chronic conditions, as physical activity is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
148
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(163 citation statements)
references
References 63 publications
10
148
0
5
Order By: Relevance
“…Although PA is a key element in the management of T2D, adherence to PA is extremely poor. A meta-analysis indicted that patients with chronic diseases had 77% adherence to the prescribed PA [13]. Another study also showed that 39% of adults with diabetes reported being physically active compared to 58% of diabetes-free adults [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although PA is a key element in the management of T2D, adherence to PA is extremely poor. A meta-analysis indicted that patients with chronic diseases had 77% adherence to the prescribed PA [13]. Another study also showed that 39% of adults with diabetes reported being physically active compared to 58% of diabetes-free adults [14].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing PA is a proven-effective strategy for both prevention as well as treatment of chronic illness [13][14][15][16]. PA has other health benefits as well, such as weight control, strengthening of muscles and bones, and improvements of physical and cognitive functioning, mental health and HRQoL-all factors negatively affected by chronic illnesses [16,17]. Despite these beneficial effects of PA, older adults are the least physically active age group, especially when they suffer from chronic illnesses [2,11].…”
Section: Introductionmentioning
confidence: 99%
“…Most of them do not reach the recommendation of 150 min per week of moderate-to-vigorous physical activity (MVPA) supplemented with muscle, bone, and balance improving activities at least twice a week [18,19]. This may be due to the many PA-related barriers (i.e., fatigue, pain) experienced by older adults with chronic illnesses [2,17]. However, meta-analyses by Bullard et al [17] and de Vries et al [10] suggest that adherence to the guidelines for PA (≥150 min of MVPA/week) is highly feasible and effective among chronic disease populations.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature by Bullard and al. showed a 77% average rate of adherence to programs 46 . As an example, the experience of the Biarritz Côte Basque Sport Health program showed that 90% pursued the practice of PA in a sports association after stopping the program 47 .…”
Section: Discussionmentioning
confidence: 99%